2018
DOI: 10.1200/jco.2017.74.1090
|View full text |Cite|
|
Sign up to set email alerts
|

Selumetinib in Combination With Dacarbazine in Patients With Metastatic Uveal Melanoma: A Phase III, Multicenter, Randomized Trial (SUMIT)

Abstract: Purpose Uveal melanoma is the most common primary intraocular malignancy in adults with no effective systemic treatment option in the metastatic setting. Selumetinib (AZD6244, ARRY-142886) is an oral, potent, and selective MEK1/2 inhibitor with a short half-life, which demonstrated single-agent activity in patients with metastatic uveal melanoma in a randomized phase II trial. Methods The Selumetinib (AZD6244: ARRY-142886) (Hyd-Sulfate) in Metastatic Uveal Melanoma (SUMIT) study was a phase III, double-blind t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
181
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(189 citation statements)
references
References 28 publications
2
181
3
3
Order By: Relevance
“…The resulting phase III (SUMIT) clinical trial with 129 patients in treatment naïve metastatic UM, comparing selumetinib + dacarbazine versus dacarbazine, did not meet its primary end point with median PFS 2.8 months vs 1.8 months (HR 0.78, 95% CI 0.48–1.27). The RR of selumetinib + dacarbazine was 3.1% compared to dacarbazine (0%) with no statistically significant benefit in OS (Carvajal et al., ).…”
Section: Oncogenic Signalingmentioning
confidence: 99%
“…The resulting phase III (SUMIT) clinical trial with 129 patients in treatment naïve metastatic UM, comparing selumetinib + dacarbazine versus dacarbazine, did not meet its primary end point with median PFS 2.8 months vs 1.8 months (HR 0.78, 95% CI 0.48–1.27). The RR of selumetinib + dacarbazine was 3.1% compared to dacarbazine (0%) with no statistically significant benefit in OS (Carvajal et al., ).…”
Section: Oncogenic Signalingmentioning
confidence: 99%
“…In a phase II clinical trial of advanced uveal melanoma, treatment with the single agent MEKi selumetinib was associated with some responses and an increase in the progression‐free survival from 7 to 16 weeks (Carvajal et al, ). Unfortunately, this was not replicated in later studies, and a trial of selumetinib plus dacarbazine failed to show any benefit over dacarbazine alone in a phase III double‐blind clinical trial (Carvajal et al, ). Studies in multiple cancers have shown that tumor cells rapidly adapt to kinase inhibitors through the adoption of a drug‐tolerant state, which is often epigenetically mediated.…”
Section: Introductionmentioning
confidence: 99%
“…Most UM tumors harbor the GNAQ or GNA11 mutations; these mutants have been shown to activate oncogenic pathways, including the mitogen-activated protein kinase (MAPK) and Hippo-Yes-associated protein (YAP) pathways [9][10][11] . Based on these studies, phase II/III clinical trials using the MEK1/2 inhibitor, selumetinib, have been conducted, but selumetinib monotherapy or combination therapy with dacarbazine has failed to increase the overall survival of patients with UM 12,13 .…”
mentioning
confidence: 99%